Dysfunction of the ciliary ARMC9/TOGARAM1 protein module causes Joubert syndrome. - Latour, Brooke L; Van De Weghe, Julie C; Rusterholz, Tamara Ds; Letteboer, Stef Jf; Gomez, Arianna; Shaheen, Ranad; Gesemann, Matthias; Karamzade, Arezou; Asadollahi, Mostafa; Barroso-Gil, Miguel; Chitre, Manali; Grout, Megan E; et al. (J Clin Invest, 2020)
Joubert syndrome (JBTS) is a recessive neurodevelopmental ciliopathy characterized by a pathognomonic hindbrain malformation. All known JBTS genes encode proteins involved in the structure or function of primary cilia, ubiquitous antenna-like organelles essential for cellular signal transduction. Here, we used the recently identified JBTS-associated protein armadillo repeat motif-containing 9 (ARMC9) in tandem-affinity purification and yeast 2-hybrid screens to identify a ciliary module whose dysfunction underlies JBTS. In addition to the known JBTS-associated proteins CEP104 and CSPP1, we identified coiled-coil domain containing 66 (CCDC66) and TOG array regulator of axonemal microtubules 1 (TOGARAM1) as ARMC9 interaction partners. We found that TOGARAM1 variants cause JBTS and disrupt TOGARAM1 interaction with ARMC9. Using a combination of protein interaction analyses, characterization of patient-derived fibroblasts, and analysis of CRISPR/Cas9-engineered zebrafish and hTERT-RPE1 cells, we demonstrated that dysfunction of ARMC9 or TOGARAM1 resulted in short cilia with decreased axonemal acetylation and polyglutamylation, but relatively intact transition zone function. Aberrant serum-induced ciliary resorption and cold-induced depolymerization in ARMC9 and TOGARAM1 patient cell lines suggest a role for this new JBTS-associated protein module in ciliary stability.
Keywords: Abnormalities, Multiple; Acetylation; Animals; Armadillo Domain Proteins; Cerebellum; Cilia; CRISPR-Cas Systems; Disease Models, Animal; Eye Abnormalities; Humans; Kidney Diseases, Cystic; Peptides; Retina; Zebrafish; Zebrafish Proteins

KMT2B-related disorders: expansion of the phenotypic spectrum and long-term efficacy of deep brain stimulation. - Cif, Laura; Demailly, Diane; Lin, Jean-Pierre; Barwick, Katy E; Sa, Mario; Abela, Lucia; Malhotra, Sony; Chong, Wui K; Steel, Dora; Sanchis-Juan, Alba; Ngoh, Adeline; Trump, Natalie; et al. (Brain, 2020)
Heterozygous mutations in KMT2B are associated with an early-onset, progressive and often complex dystonia (DYT28). Key characteristics of typical disease include focal motor features at disease presentation, evolving through a caudocranial pattern into generalized dystonia, with prominent oromandibular, laryngeal and cervical involvement. Although KMT2B-related disease is emerging as one of the most common causes of early-onset genetic dystonia, much remains to be understood about the full spectrum of the disease. We describe a cohort of 53 patients with KMT2B mutations, with detailed delineation of their clinical phenotype and molecular genetic features. We report new disease presentations, including atypical patterns of dystonia evolution and a subgroup of patients with a non-dystonic neurodevelopmental phenotype. In addition to the previously reported systemic features, our study has identified co-morbidities, including the risk of status dystonicus, intrauterine growth retardation, and endocrinopathies. Analysis of this study cohort (n = 53) in tandem with published cases (n = 80) revealed that patients with chromosomal deletions and protein truncating variants had a significantly higher burden of systemic disease (with earlier onset of dystonia) than those with missense variants. Eighteen individuals had detailed longitudinal data available after insertion of deep brain stimulation for medically refractory dystonia. Median age at deep brain stimulation was 11.5 years (range: 4.5-37.0 years). Follow-up after deep brain stimulation ranged from 0.25 to 22 years. Significant improvement of motor function and disability (as assessed by the Burke Fahn Marsden's Dystonia Rating Scales, BFMDRS-M and BFMDRS-D) was evident at 6 months, 1 year and last follow-up (motor, P = 0.001, P = 0.004, and P = 0.012; disability, P = 0.009, P = 0.002 and P = 0.012). At 1 year post-deep brain stimulation, >50% of subjects showed BFMDRS-M and BFMDRS-D improvements of >30%. In the long-term deep brain stimulation cohort (deep brain stimulation inserted for >5 years, n = 8), improvement of >30% was maintained in 5/8 and 3/8 subjects for the BFMDRS-M and BFMDRS-D, respectively. The greatest BFMDRS-M improvements were observed for trunk (53.2%) and cervical (50.5%) dystonia, with less clinical impact on laryngeal dystonia. Improvements in gait dystonia decreased from 20.9% at 1 year to 16.2% at last assessment; no patient maintained a fully independent gait. Reduction of BFMDRS-D was maintained for swallowing (52.9%). Five patients developed mild parkinsonism following deep brain stimulation. KMT2B-related disease comprises an expanding continuum from infancy to adulthood, with early evidence of genotype-phenotype correlations. Except for laryngeal dysphonia, deep brain stimulation provides a significant improvement in quality of life and function with sustained clinical benefit depending on symptoms distribution.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Cohort Studies; Computer Simulation; Deep Brain Stimulation; Disease Progression; Dystonic Disorders; Endocrine System Diseases; Female; Fetal Growth Retardation; Gait Disorders, Neurologic; Histone-Lysine N-Methyltransferase; Humans; Laryngeal Diseases; Male; Mutation; Mutation, Missense; Phenotype; Quality of Life; Treatment Outcome; Young Adult